Clinical outcomes of single incision laparoscopic surgery for colorectal cancer: A propensity score‐matched analysis between well‐experienced and novice surgeons. Issue 1 (5th August 2022) - Tei, Mitsuyoshi; Suzuki, Yozo; Ohtsuka, Masahisa; Iwamoto, Kazuya; Naito, Atsushi; Imasato, Mitsunobu; Mizushima, Tsunekazu; Akamatsu, Hiroki
Abstract: Background: Single incision laparoscopic surgery (SILS) is a recent advancement in minimally invasive techniques for colorectal cancer (CRC). However, SILS is a technically challenging procedure for novice surgeons. The aim of this study was to evaluate clinical outcomes of SILS for CRC performed by novice surgeons compared with those performed by well‐experienced surgeons. Methods: We retrospectively analyzed 1004 consecutive patients with stage I‐IV CRC who underwent SILS between May 2009 and December 2018, using propensity score‐matched analysis. Results: After propensity score‐matching, we enrolled 344 patients (n = 172 in each group). Before matching, significant group‐dependent differences were observed in terms of age ( P  = 0.034) and tumor location ( P  < 0.001). After matching, preoperative clinical factors were similar between groups, but operative time was longer in the Novice group (213 vs 171 min, P  < 0.001). Other operative factors and morbidity rates did not differ significantly between groups. The number of harvested lymph nodes was smaller in the Novice group (23 vs 25, P  = 0.040), and the number of patients with lymph node metastases was smaller in the Novice group (57 vs 86, P  = 0.002). The 3‐year disease‐free survival rate was 85.8% in the Novice group and 89.9% in the Experienced group ( P  = 0.512). Three‐year overall survival rate was 92.2% in the Novice group and 90.0% in the Experienced group ( P  = 0.899). Conclusion: SILS for CRC was safely performed by novice surgeons under the guidance of well‐experienced surgeons, and could provide satisfactory oncological outcomes. Abstract : SILS is a technically challenging procedure for novice surgeons. We evaluate the clinical outcomes of SILS for colorectal cancer performed by novice surgeons. SILS was safely performed by novice surgeons under the guidance of well‐experienced surgeons, and could provide satisfactory oncological outcomes.